Strategic family therapy - Golden Triad Films (Kansas City : Golden Triad Films, 1986)
Strategic family therapy, which owes much to communications theory and to the planful strategies of Milton Erickson, the therapist takes charge of the therapy
Video is accompanied by 1 study guide, title: The major theories of family therapy
Presenter: Laurence G. Ro-Trock, Ramon G. Corrales ; Narrator: Ray R. Price
Keywords: Family psychotherapy; Structural-strategic family psychotherapy